First island species of Hyalella (Amphipoda, Hyalellidae) from Florianópolis, state of Santa Catarina, Southern Brazil - Rangel, Carolina; Da Silva, Aurea Luiza Lemes; Siegloch, Ana Emília; Limberger, Márcio; Da Silva Castiglioni, Daniela (Zootaxa, 2022)
The Hyalella comprises a group of freshwater amphipods endemic to the Americas. In Brazil, the greatest diversity of species known so far is concentrated in the state of Rio Grande do Sul, but recently discoveries were made in the neighboring state of Santa Catarina. The present work describes the first island species of the genus Hyalella in Brazil and the fifth with occurrence in the state of Santa Catarina. The species was found in streams of two watersheds, located at the Monumento Natural Municipal da Lagoa do Peri, an important environmental protection area on the island of Florianópolis, Southern Brazil. Hyalella insulae n. sp. shows the following characters: inner face of propodus of gnathopod 1 with 7 serrate setae, gnathopod 2 with propodus ovate, peduncle of uropod 3 with 10 cuspidate setae, telson rectangular, wider than long, with 6 cuspidate setae and 2 plumose setae laterally close to each distal seta. H. insulae n. sp. differs from the other species with occurrence in Santa Catarina, H. catarinensis, H. rioantensis, H. sambaqui and H. lagoana, mostly concerning to the number and shape of setae of the gnathopods, uropods and telson. A comparison was also made with species from the neighboring states, Rio Grande do Sul and Paraná. The description of H. insulae n. sp. in the present study contributes to increasing the knowledge of the Hyalella diversity in the state of Santa Catarina, little known so far.